Dosimetric benefits of adaptive radiation therapy for patients with stage III non-small cell lung cancer - Hoppen, Lea; Sarria, Gustavo R.; Kwok, Chung S.; Boda-Heggemann, Judit; Bürgy, Daniel; Ehmann, Michael; Giordano, Frank Anton; Fleckenstein, Jens (Radiation oncology, 2023)
Daily adaptive radiation therapy (ART) of patients with non-small cell lung cancer (NSCLC) lowers organs at risk exposure while maintaining the planning target volume (PTV) coverage. Thus, ART allows an isotoxic approach with increased doses to the PTV that could improve local tumor control. Herein we evaluate daily online ART strategies regarding their impact on relevant dose-volume metrics. Daily cone-beam CTs (1 × n = 28, 1 × n = 29, 11 × n = 30) of 13 stage III NSCLC patients were converted into synthetic CTs (sCTs). Treatment plans (TPs) were created retrospectively on the first-fraction sCTs (sCT1) and subsequently transferred unaltered to the sCTs of the remaining fractions of each patient (sCT2−n) (IGRT scenario). Two additional TPs were generated on sCT2−n: one minimizing the lung-dose while preserving the D95%(PTV) (isoeffective scenario), the other escalating the D95%(PTV) with a constant V20Gy(lungipsilateral) (isotoxic scenario). Compared to the original TPs predicted dose, the median D95%(PTV) in the IGRT scenario decreased by 1.6 Gy ± 4.2 Gy while the V20Gy(lungipsilateral) increased in median by 1.1% ± 4.4%. The isoeffective scenario preserved the PTV coverage and reduced the median V20Gy(lungipsilateral) by 3.1% ± 3.6%. Furthermore, the median V5%(heart) decreased by 2.9% ± 6.4%. With an isotoxic prescription, a median dose-escalation to the gross target volume of 10.0 Gy ± 8.1 Gy without increasing the V20Gy(lungipsilateral) and V5%(heart) was feasible. We demonstrated that even without reducing safety margins, ART can reduce lung-doses, while still reaching adequate target coverage or escalate target doses without increasing ipsilateral lung exposure. Clinical benefits by means of toxicity and local control of both strategies should be evaluated in prospective clinical trials.